Analysis of LKjIP performance measurement with the value for money concept at Bappeda Bali Province - Ni Made Ari Dwi Anggraeni; I Dewa Made Mahayana; Paulus Subiyanto (Journal of Applied Sciences in Accounting, Finance, and Tax, 2023)
This study aims to measure the performance of Laporan Kinerja Instansi Pemerintah (LKjIP) with the concept of value for money at the Regional Development Planning Agency (Bappeda) of Bali Province. Performance measurement in the public sector is important to determine accountability and can improve the quality of public services. Government agencies that have carried out performance measurement need to report it in the form of LKjIP. To ensure that the performance achievements in LKjIP are correct, it is necessary to re-measure performance using the concept of value for money. Value for money is useful for checking whether the performance of the Bali Province Bappeda LKjIP in 2021 and 2022 has fulfilled the principles of economically, efficiently, and effectively. This research uses a qualitative method. Data collection was carried out by unstructured interviews and documentation in the form of LKjIP in 2021 and 2022. The analysis technique used is descriptive analysis technique by conducting a process of data collection, data reduction, data presentation, and conclusion drawing. The results showed that the performance of the Bappeda Bali Province LKjIP in 2021 and 2022 in terms of economy was categorized as economical, in terms of efficiency it was categorized as efficient, and in terms of effectiveness it was categorized as effective. This research is expected to provide a consideration for the government to pay more attention to performance in terms of economy, efficiency, and effectiveness. This is intended in achieving LKjIP performance not only in terms of the main performance indicators.